A new paradigm for predictive functional control to enable more consistent tuning - Rossiter, John Anthony; Abdullah, Muhammad (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper presents two significant contributions to the understanding of Predictive Functional Control (PFC). First, it gives novel insights and explanations into a poorly understood issue, that is the weak link between PFC tuning parameters and the resulting closed-loop behaviour. This new understanding is then exploited to proposed a modification to the existing PFC algorithm which creates a much stronger tuning link while retaining the critical properties of elementary coding and understanding. The efficacy of the proposal is demonstrated on several numerical examples.